The Question of Principalities in Kyivan Rus’ - Torres Prieto, Susana (Institute of History of Ukraine, 2025)
The present article is the result and, to a certain extent, an example of the challenges posed by the use of digital humanities in the field of medieval studies. Digital humanities, as a new methodology, if properly used, should contribute to the fruitful opening of new avenues for research. Otherwise, it is just solipsistic entertainment.
Keywords: 55 Historia::5504 Historia por épocas::5504.03 Historia medieval; ODS 11 - Ciudades y comunidades sostenibles